Perioperative Management and In-Hospital Outcomes After Minimally Invasive Repair of Pectus Excavatum: A Multicenter Registry Report From the Society for Pediatric Anesthesia Improvement Network. (February 2019) - Muhly, Wallis T.; Beltran, Ralph J.; Bielsky, Alan; Bryskin, Robert B.; Chinn, Christopher; Choudhry, Dinesh K.; Cucchiaro, Giovanni; Fernandez, Allison; Glover, Chris D.; Haile, Dawit T.; Kost-Byerly, Sabine; Schnepper, Gregory D.; et al.
Abstract : BACKGROUND: There are few comparative data on the analgesic options used to manage patients undergoing minimally invasive repair of pectus excavatum (MIRPE). The Society for Pediatric Anesthesia Improvement Network was established to investigate outcomes for procedures where there is significant management variability. For our first study, we established a multicenter observational database to characterize the analgesic strategies used to manage pediatric patients undergoing MIRPE. Outcome data from the participating centers were used to assess the association between analgesic strategy and pain outcomes. METHODS: Fourteen institutions enrolled patients from June 2014 through August 2015. Network members agreed to an observational methodology where each institution managed patients based on their institutional standards and protocols. There was no requirement to standardize care. Patients were categorized based on analgesic strategy: epidural catheter (EC), paravertebral catheter (PVC), wound catheter (WC), no regional (NR) analgesia, and intrathecal morphine techniques. Primary outcomes, pain score and opioid consumption by postoperative day (POD), for each technique were compared while adjusting for confounders using multivariable modeling that included 5 covariates: age, sex, number of bars, Haller index, and use of preoperative pain medication. Pain scores were analyzed using repeated-measures analysis of variance with Bonferroni correction. Opioid consumption was analyzed using a multivariable quantile regression. RESULTS: Data were collected on 348 patients and categorized based on primary analgesic strategy: EC (122), PVC (57), WC (41), NR (120), and intrathecal morphine (8). Compared to EC, daily median pain scores were higher in patients managed with PVC (POD 0), WC (POD 0, 1, 2, 3), and NR (POD 0, 1, 2), respectively ( P < .001–.024 depending on group). Daily opioid requirements were higher in patients managed with PVC (POD 0, 1), WC (POD 0, 1, 2), and NR (POD 0, 1, 2) when compared to patients managed with EC ( P < .001). CONCLUSIONS: Our data indicate variation in pain management strategies for patients undergoing MIRPE within our network. The results indicate that most patients have mild-to-moderate pain postoperatively regardless of analgesic management. Patients managed with EC had lower pain scores and opioid consumption in the early recovery period compared to other treatment strategies.